Implementation of the Independent Curriculum for Early Childhood at SPS Permata Hati Bekasi - Defi, Sri; Mulyanti, Fitrah; Azzahri, Childa Kumala (Bulletin of Early Childhood, 2025)
This study analyzed the implementation of the Independent Curriculum (Kurikulum Merdeka) in Early Childhood Education (PAUD) at SPS Permata Hati Bekasi. Using a descriptive qualitative approach with a case study design, the research explored several key aspects, including curriculum planning, implementation strategies, challenges encountered, and the resulting impact on teaching and learning. The findings indicated that the planning stage was carried out thoroughly, with the school successfully developing relevant learning programs and aligning activities with the principles of the Independent Curriculum. Despite this strong planning, the actual implementation did not reach its full potential. Teachers relied heavily on traditional, teacher-centered methods, which limited the effectiveness of student-centered learning approaches. As a result, some students experienced confusion, and the intended learning outcomes of the curriculum were not fully realized. The study highlighted the importance of enhancing pedagogical strategies that prioritized active student engagement, providing continuous professional development and training for teachers, and optimizing the use of diverse learning resources. By addressing these areas, the school could better achieve the objectives of the Independent Curriculum, fostering more meaningful and effective learning experiences for young children.